Hateship, friendship, courtship, loveship, marriage stories - Munro, Alice 1931- (New York Vintage Contemporaries, 2002)
A collection of short fiction explores the complexities of human relationships and emotions in stories about a housekeeper entering old-maidhood whose life is transformed by a practical joke and a lifelong philanderer who finds the tables turned.
Hateship, friendship, courtship, loveship, marriage -- Family furnishings -- Comfort -- Queenie -- Nettles -- Post and beam -- What is remembered -- The bear came over the mountain.
UCWS-2014-G-1702 donated by Gay Benueza
Keywords: Women -- Canada -- Fiction; Women -- Psychology -- Fiction; Canada -- Social life and customs -- 20th century -- Fiction